Investigating the Impact of Flipped Learning on Mathematics Performance and Math Anxiety - Deliktas, Yilmaz; Stojkovska, Irena (Природно-математички факултет, Скопје, 2019)
Education system, whose aim is to prepare students for their future life, always lags behind changes at the societal, economic and personal levels and has difficulty in meeting their expectations. Educators must be challenged to discover new ways of thinking about education and they must be encouraged to apply new methods and techniques in the classroom. Traditional forms of classroom instruction limit the interaction between students, favoring only student-teacher interactions and students struggle with learning the content. Flipped classroom offers a solution for the issue, as its practice incorporates well with the new learning expectations. This study is an attempt to answer the following major questions: Do students learn more in flipped mathematics classrooms? Does flipped classroom decrease the math anxiety level of the students? The one semester study was conducted with 82 first year high school students from four classes divided in a control and an experimental study groups. The classes in the control group were taught by traditional method and the classes in the experimental group were taught according to flipped classroom strategy. After the experiment, the results reveal statistically significant difference of the mathematics achievement test scores between the experimental and the control groups, in favor of the experimental group, and statistically significant reduction of the math anxiety level only in the experimental group.
Keywords: Flipped Learning, Mathematics Performance, Math Anxiety